2019
DOI: 10.1002/jper.19-0105
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep and severe periodontitis in a nationally representative adult US population

Abstract: BackgroundPoor sleep behavior appears to have adverse effects on health by metabolic disruption and immunity suppression. Sleep disturbance is strongly associated with diabetes, cardiovascular diseases, and some cancers. This study aimed to evaluate the association between sleep duration and periodontal disease in a national US population study in a National Health and Nutrition Examination Survey (NHANES).MethodsThe data were collected from individuals aged ≥30 years and included 3,624 participants in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…Several cross-sectional studies have reported an association between sleep quality and duration, and periodontal disease among different age groups (mean age in each group; ≥ 30 years) [9][10][11][12][13][14]. However, our results coincided with those of only one previous report [15].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Several cross-sectional studies have reported an association between sleep quality and duration, and periodontal disease among different age groups (mean age in each group; ≥ 30 years) [9][10][11][12][13][14]. However, our results coincided with those of only one previous report [15].…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, in this study, we excluded a very small number of smokers and alcohol drinkers because there is evidence of influence of smoking and drinking on sleep quality and duration [27,28]. By contrast, some previous studies treated these behaviours as covariates [9][10][11]14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Sleep disturbance and sleep time duration in night-shift workers may thus have a relationship with periodontal health status, and diabetes may modify this association. 15 No previous evidence-based data exists regarding the effects of sleep time duration on oral inflammation and periodontal health status in night-shift workers. On this basis, an analysis of sleep time duration in night-shift workers in relation to salivary melatonin and its effects on salivary MDA and salivary TNF-α as oral inflammation indicators, together with depth of pocket and bleeding on probing (BOP) as periodontal health status indicators, need to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of the included studies (N = 8) investigated the association between short sleep duration and periodontal disease. The results of four studies showed that periodontal disease was directly related to short sleep duration [32,34,37,42]. Although the remaining four studies reported no significant association between periodontitis and sleep duration in fully adjusted models, two of them showed a significant association in unadjusted model and one of them showed an obvious trend in this regard [33,40,43,44].…”
Section: Short Sleep Durationmentioning
confidence: 96%